2014
DOI: 10.1002/mawe.201400246
|View full text |Cite
|
Sign up to set email alerts
|

Properties of cotton/T‐400 and 100% cotton plain knitted fabric made from ring spun yarn

Abstract: This research studies the properties of a plain knitted fabric made from cotton/T‐400 ring core spun yarn and 100% cotton ring spun yarn. Properties of plain knitted fabric made from 100% cotton ring spun yarn were compared with one made from cotton/T‐400 (70.4C/29.6T). We focused on knitted fabric properties such as the bursting strength, elongation at break, tensile strength, air permeability as well as pilling properties. The two yarn samples were produced on the ring frame which had a special attachment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…17 There were a few studies on using T400 as a core component of core-spun yarn and fabrics produced from them. [17][18][19] Lately, new types of core yarns called dual-core spun yarns have been introduced. Dual-core yarns can be defined as a multicomponent core-spun yarn composed of two different core components.…”
mentioning
confidence: 99%
“…17 There were a few studies on using T400 as a core component of core-spun yarn and fabrics produced from them. [17][18][19] Lately, new types of core yarns called dual-core spun yarns have been introduced. Dual-core yarns can be defined as a multicomponent core-spun yarn composed of two different core components.…”
mentioning
confidence: 99%
“…Air permeability is considered an important comfort parameter for a wearer, which is influenced by the thickness, weight and structure of the fabric. Fibre content and the inter-yarn pores (texture, size, shape) between individual yarns have a significant effect on air permeability [30,31].…”
Section: Introduction *mentioning
confidence: 99%
“…Telli et al, focused on the usage of core and double-core yarns containing tungsten for electromagnetic shielding [12]. Akankwasa et al focused on the mechanical properties of cotton/T400® knitted fabrics and reported that fabrics knitted from cotton/T400® yarns are advantageous in breaking elongation, bursting strength and air permeability compared to 100% cotton yarns [13]. Cataloglu stated that, alternative to elastane, using bi-component polyester fibres and poly butylene terephthalate (PBT) has inspired interest with regarding to higher strength due to better chemical resistance, better recovery, dimensional stability and elasticity properties [14].…”
Section: Introductionmentioning
confidence: 99%